Conformação viscoplástica por rolos a frio e caracterização de substratos de alumina - Koshimizu, Laís (Universidade Federal de São Carlos, 2008)
Alumina ceramic substrates were conformed by viscoplastic conformation by cold roll pressing in a range of thickness between 100 and 200 µm, which one presents a great technology interesting for eletro-eletronic applications. Among all the techniques of ceramic conformation the viscoplastic processing shows great advantages, allowing the conformation oh ceramic bodies with superior mechanical properties, when compared to the bodies conformed by traditional techniques, such as extrusion, or more complex as tape casting. In this scope, the objective of this work was to verify the potential of viscoplastic conformation by cold roll pressing as a technique to obtain thin substrates, from a high alumina plastic mass prepared in a sigma mixer and extruded by vacuum. In this way, parameters process such as the speed of the rollers and the thickness of the substrates were evaluated, as well as the stages of shrinkage and firing. The final samples were characterized by determination of the microstructure, apparent density and porosity, volume retraction, penetrating liquid and surface roughness. The results showed that the speed of rollers around 15 and 18 rpm provided substrates without the presence of macro defects. Moreover, there s no correlation between the thickness of the substrates and the final characteristics after sinterization, and there s no preferential orientation of the particles when the mass of submitted to plastic deformation. Density superior to 95% of theoretical density were achieved, producing translucent samples and a great homogeneity of the grain size. After the establishment of best conditions for preparation of alumina substrates, they have been applied in the preparation of zirconia substrates with reproducibility of the results, showing that the viscoplastic processing by roll pressing can be an alternative process for the manufacture of ceramic substrates.
Viscoplastic conformation by cold roll pressing and characterization of alumina substrats
Keywords: Cerâmica (Tecnologia); Processamento cerâmico; Filmes finos; Alumina; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA